Evaluation of a wind energy based system for co-generation of hydrogen and methanol production. (11th June 2020) - Ishaq, Haris; Dincer, Ibrahim
Abstract: A novel idea of wind energy based methanol and hydrogen production is proposed in this study. The proposed system utilizes the industrial carbon emissions to produce a useful output of methanol. There are several pros of manufacturing the methanol as it has the capability to be employed as conventional automotive fuel as it carries the advantages of efficient performance, low emissions and low flammability risk. The designed system comprises of the major subsystems of wind turbines, proton exchange membrane fuel cell (PEMFC), methanol production system and distillation unit. The Engineering Equation Solver (EES) and Aspen Plus are utilized for system modeling and comprehensive analysis. The proposed system is also investigated to operate under different wind speeds and different wind turbine efficiencies. The proposed integration covers all the electric power required by the system. The industrial flue gas including CO2 reacts with hydrogen to produce methanol. The designed system produces both methanol and hydrogen simultaneously. For the performance indicator, efficiencies of the overall system are calculated. The exergetic efficiency is found to be 38.2% while energetic efficiency is determined to be 39.8%. Furthermore, some parametric studies are conducted to investigate the distillation column performance, methanol and hydrogen capacities and exergy destruction rates. Highlights: A novel idea of wind energy based methanol and hydrogen production is proposed. The industrial flue gas including CO2 reacts with hydrogen to produce methanol. This novel integration reduces 2999 ton/yr of CO2 emissions. The designed system produces 3.4 g/s of hydrogen and 52.25 g/s of methanol. Exergetic and energetic efficiencies are found to be 40.5% and 42.3% respectively.